Sodium pyruvate exerts protective effects against cigarette smoke extract-induced ferroptosis in alveolar and bronchial epithelial cells through the GPX4/Nrf2 axis - Ziwen Zhao; Zhao Xu; Jingwen Chang; Liwei He; Zijin Zhang; Xiaoyu Song; Xianbang Hou; Fangtian Fan; Zhijun Jiang (Journal of Inflammation, 2023)
Abstract Background Ferroptosis in alveolar and bronchial epithelial cells is one of the main mechanisms underlying the development of chronic obstructive pulmonary disease (COPD). Sodium pyruvate (NaPyr) is a natural antioxidant in the body, exhibiting anti-inflammatory and antioxidant activities. NaPyr has been used in a Phase II clinical trial as a novel therapy for COPD; however, the mechanism underlying NaPyr-mediated therapeutic benefits in COPD is not well understood. Objective We aimed to assess the protective effects of NaPyr and elucidate its potential mechanism in cigarette smoke extract (CSE)-induced ferroptosis.To minic the inflammatory response and ferroptosis triggered by cigarette smoke in COPD in an invitro cell based system, we expose a human bronchial epithelial cells to CSE. Methods To minic the inflammatory response and ferroptosis triggered by cigarette smoke in COPD in an invitro cell based system, the A549 (human lung carcinoma epithelial cells) and BEAS-2B (bronchial epithelial cells) cell lines were cultured, followed by treatment with CSE. To measure cellular viability and iron levels, we determined the levels of malondialdehyde (MDA), glutathione (GSH), reactive oxygen species (ROS), mitochondrial superoxide (MitoSOX), membrane potential (MMP), and inflammatory factors (tumor necrosis factor [TNF] and interleukin [IL]-8), and examined CSE-induced pulmonary inflammation and ferroptosis. To clarify the molecular mechanisms of NaPyr in COPD therapy, we performed western blotting and real-time PCR (qPCR) to determine the expression of glutathione peroxidase 4 (GPX4), nuclear factor E2-related factor 2 (Nrf2), and cyclooxygenase 2 (COX2). Results We found that NaPyr effectively mitigated CSE-induced apoptosis and improved apoptosis induced by erastin, a ferroptosis inducer. NaPyr significantly decreased iron and MDA levels and increased GSH levels in CSE-induced cells. Furthermore, NaPyr suppressed ferroptosis characteristics, such as decreased levels of ROS, MitoSOX, and MMP. NaPyr significantly increases the expression levels of GPX4 and Nrf2, indicating that activation of the GPX4/Nrf2 axis could inhibit ferroptosis in alveolar and bronchial epithelial cells. More importantly, NaPyr inhibited the secretion of downstream inflammatory factors, including TNF and IL-8, by decreasing COX2 expression levels to suppress CSE-induced inflammation. Conclusion Accordingly, NaPyr could mitigate CSE-induced ferroptosis in alveolar and bronchial epithelial cells by activating the GPX4/Nrf2 axis and decreasing COX2 expression levels. In addition, NaPyr reduced the secretion of inflammatory factors (TNF and IL-8), affording a novel therapeutic candidate for COPD. Graphical Abstract